2019
DOI: 10.1089/ten.tea.2018.0223
|View full text |Cite
|
Sign up to set email alerts
|

Poly(Thioketal Urethane) Autograft Extenders in an Intertransverse Process Model of Bone Formation

Abstract: Iliac crest autograft (AG) is the gold standard for bone grafting. Due to the limited supply of autograft, synthetic materials such as ceramics and polymers have been proposed as AG extenders to minimize the volume of AG required for induction of new bone formation. However, the feasibility of reactive polymers for use as settable AG extenders has not been previously investigated. In this study, a reactive oxygen species-degradable poly(thioketal urethane) (PTKUR) was evaluated as a settable AG extender. AG wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 69 publications
1
13
0
Order By: Relevance
“…In agreement with an earlier PTKUR-AG study in a biologically stringent intertransverse process defect [ 39 ], residual polymer was observed in PTKUR-AG extenders at 12 weeks. PEUR degradation occurred more rapidly than PTKUR degradation, as evidenced by significantly less residual polymer within the defect at 12 weeks.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In agreement with an earlier PTKUR-AG study in a biologically stringent intertransverse process defect [ 39 ], residual polymer was observed in PTKUR-AG extenders at 12 weeks. PEUR degradation occurred more rapidly than PTKUR degradation, as evidenced by significantly less residual polymer within the defect at 12 weeks.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies in the spine and mandible demonstrated that an elastic modulus >1 MPa provided compression-resistant properties [ 46 , 47 ]. We previously reported PTKUR-AG and PEUR-allograft moduli of 6.08 MPa and 4.38–9.47 MPa, respectively [ 39 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Polymers have also been designed to degrade upon exposure to reactive oxygen species for use in drug delivery, biosensing, and tissue engineering applications. 8,[23][24][25][26][27] The methods described here could be used to evaluate degradation products from these systems for toxicity or for their impact on the desired outcomes after implantation. These methods may also be useful in evaluating other polymers that may degrade by oxidation as one of multiple mechanisms as is proposed of some other polyurethane scaffolds and poly (ethylene glycol) hydrogels.…”
Section: Discussionmentioning
confidence: 99%